Studies in Australian Tettigoniidae: Ozphyllum, a new genus of Phaneropterine katydids with comments on its relationships and ecology (Orthoptera: Tettigoniidae; Phaneropterinae) - Rentz, D. C.f.; Su, You Ning; Ueshima, Norhiro (Zootaxa, 2007)
A new genus of phaneropterine Tettigoniidae, Ozphyllum Rentz, Su, & Ueshima gen. nov., is described with two species known from rainforest and wallum habitats along the east coast of northern New South Wales and Queensland. The new genus appears to be most closely related to Cosmophyllum Blanchard from Chile. Detailed descriptions of the new species and notes on their ecology, cytology and song are presented. A table helps to separate the two species.